Le Régime social britannique à l’heure du Brexit, entre complexité constitutionnelle et incertitude politique - Clémence Fourton (Revue Française de Civilisation Britannique, 2021)
This article considers the effects of the United Kingdom’s exit from the European Union on the British welfare regime, in other words the country’s social institutions, together with their effects and determiners. In particular, the repatriation of European competences, the integration and reform of the acquis communautaire, and the break from European institutions raise questions of governance and political equilibria, since these developments take place against a constitutional backdrop characterized by an absence of codification as well as the devolution of some executive and legislative powers to the British nations. After Brexit, the differentiation between the English, Scottish, Welsh and Northern Irish welfare regimes is therefore bound to increase. The United Kingdom will also have to come up with new mechanisms in order to mitigate regional inequalities, lest these keep growing. Outside of the EU, social rights are no longer protected by the European Court of Justice, and are back within the remit of parliamentary sovereignty. The British welfare regime is thus more than ever subjected to conjunctural balances of power, these being marked, by, among other things, the temptation of power concentration in London, the conservative inheritance in terms of social policy, and logics of territorial differentiation. Last but not least, the process of exiting the EU provokes, jointly with its enhanced politicization, a lack of visibility as to the definition of British social policy in the medium and longer term.